Analisis Pengaruh Procedural Justice, Distributive Justice, dan Satisfaction Terhadap Organizational Citizenship Behavior (OCB) dengan Affective Commitment Sebagai Variabel Mediasi - Abdul Aziz (Universitas Ngudi Waluyo, 2020)
The purpose of this study was to examine the effect of Procedural Justice, Distributive Justice, and Satisfaction on Organizational Citizenship Behavior (OCB) with Affective Commitment as a Mediating Variable on the employees of PT. Hartono Istana Teknologi in the Goods Warehouse Division. This research is an explanatory research with a causality approach, namely research that wants to find an explanation in the form of cause-effect relationships. The sample of this study was 84 respondents determined by the Purposive Random Sampling method. The research data were obtained from distributing questionnaires with multiple linear regression analysis tools with SPSS Version 21. The results of this study indicate that there are positive and significant influences between the variables of Procedural Justice, Distributive Justice and Satisfaction with Organizational Citizenship Behavior (OCB). And the role of affective commitment as a moderating variable can strengthen the influence of Procedural Justice, Distributive Justice and Satisfaction with Organizational Citizenship Behavior (OCB)